Inhibitory action of dried leaf of Cassia alata (Linn.) Roxb against lipoxygenase activity and nitric oxide generation - Oso, Babatunde (2019)
The mechanisms of inflammation mediated by metabolites of lipoxygenase and nitric oxide play essential roles in physiological immune response. The aim of this study was to evaluate the lipoxygenase (LOX) inhibitory activity of methanolic extract of dried leaf of Cassia alata (Linn.) Roxb. as well as its effect on in vitro accumulation of nitric oxide (NO). The LOX inhibitory activity was evaluated for its ability to inhibit lipoxygenase (soyLOX) by absorbance-based assay using linoleic acid as the substrate while the influence of the extract on accumulation of NO was monitored spectrophotometrically by Griess assay method. Moreover, gas chromatographic analysis was carried out on the ether extract to identify and quantify the volatile compounds in the extract. The study showed effective soyLOX inhibitory activity correlating with the NO depletion in a concentration-dependent manner. The gas chromatographic identification of the volatile compounds in the extract showed the presence of stearic, oleic and linoleic acids. This study revealed the methanolic extract of the leaf of C. alata (Linn.) Roxb. as potent inhibitor of both soyLOX and nitric oxide generation. Thus, these results give indications regarding therapeutic interest of C. alata (Linn.) Robx. as a potential anti-inflammatory agent.